Pengaruh Gaya Kepemimpinan Transformasional Terhadap Efektivitas Pelaksanaan Program Dana Desa Pada Desa Apung dan Desa Mara Hilir Kabupaten Bulungan: Partisipasi Masyarakat Sebagai Variabel Mediasi - Bagus Haryanto, Rino; Daulay, Pardamean; Yulianti, Rina (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2026)
The implementation of the Village Fund Program in Bulungan Regency, North Kalimantan Province, faces challenges regarding low community involvement. Initial observations in Apung and Mara Hilir Villages revealed a contrast in leadership approaches, where one village tended toward a rigid instructional style while the other was more participatory, which is suspected to cause variations in program effectiveness.This study aims to analyze how the leadership style of the village head influences the effectiveness of the Village Fund Program, both directly and indirectly, through community participation as a mediating variable. The research utilized a quantitative approach with an associative design. The population consisted of community beneficiaries of the Village Fund Program from two villages, Apung and Mara Hilir in Bulungan Regency, totaling 212 respondents. Data were collected using a Likert-scale questionnaire and analyzed through Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with Jamovi software. The results indicate that the village head’s leadership style has a positive and significant effect on community participation, as well as both direct and indirect effects on program effectiveness through this participation. The coefficient of determination reveals that 67.8% of the variation in program effectiveness can be explained by leadership and community participation, while the remaining 32.2% is influenced by other factors. These findings suggest that a transformational and participatory leadership style encourages active community involvement, thereby enhancing the effectiveness and sustainability of rural development programs.